Reimagining Future Island: The COVID-19 Impacts on Tourism Sector in Small Island Developing States (SIDS) and Strategies to Moving Forward - Reksa, Abdul Fikri Angga; Lissandhi, Ayu Nova; Syahid, Choerunisa Noor (RMPI-BRIN, 2021)
The COVID-19 pandemic has ravaged the global tourism industry, leaving millions of people unemployed without certainty when tourism bounces back. Small Island Developing States (SIDS) are amongst the worst hit by the novel coronavirus. The unprecedented crisis has severely aggravated the SIDS economic growth due to relying on foreign tourists heavily. In the absence of international tourism, small island residents have been grappling with alternative income sources. Despite its notorious impacts, many scholars look at this global pandemic as a discernible opportunity to reverse mass tourism in the SIDS. Therefore, this paper aims to elaborate on the current condition of small islands communities amid COVID-19, their coping strategies, and their reflection of the future tourism industry in the SIDS. Furthermore, this paper also aims to discuss a prevailing policy to contain health emergency and economic collapse in the SIDS. Based on the critical literature review, many SIDS were already faced complex predicaments before the pandemic, such as high vulnerability to the climate crisis, lack of natural resources, extreme poverty, and reliance on external debts. International support is crucial to avoid the worst-case scenario for SIDS, including those which depend on the tourism industry. As a part of the recovery phase, this paper underscores the urgency of a more sustainable tourism practice for future development in the SIDS. That comprises strategic issues ranging from environmental-based tourism with a focus on socio-cultural aspects, and economic diversification to small island community resilience.